Economic Viability Analysis of Silicon Solar Cell Manufacturing: Al-BSF versus PERC. (September 2017) - Kumar, Abhishek; Bieri, Monika; Reindl, Thomas; Aberle, Armin G.
Abstract: The International Technology Roadmap for Photovoltaic (ITRPV) predicts that the worldwide market share of the PERC silicon solar cell technology will grow to about 40% by 2021. In line with this forecast, several solar companies have announced new investments into manufacturing capacity for PERC cells. Though higher in terms of efficiency, the economic success of the PERC technology - against the incumbent Al-BSF technology - is strongly dependent on the $/Wp cost to manufacture it. Moreover, currently the solar cell industry is dominated by p -type multi-Si BSF cell technology, due to the historically lower cost of block-cast multi-Si wafers compared to crystalline Cz mono-Si wafers. Recently there has been a sharp decline in the cost of mono-Si wafers, making mono-Si cells more cost-competitive to multi-Si cells. We use a comprehensive life-cycle cell cost model, developed in SERIS, to calculate break-even $/Wp to manufacture p -type multi-Si Al-BSF and PERC cells. The model takes into account the total life-cycle cost of a 1-GWp production capacity operating for seven years, including manufacturing cost (e.g. consumables, O&M) and financing cost. The output data aligns well with the historical trend in the ITRPV, and thus the model was expanded to compare the $/Wp cost of manufacturing p-type multi-Si and mono-Si PERC cells. Our calculations indicate that cost to manufacture p -type multi-Si PERC cells is ~0.7 $-cents/Wp higher than p -type multi-Si BSF cells. The increase in cost is primarily due to additional processing steps requiring higher capital and labor cost, but partially compensated by the lower $/Wp costs of the wafers and the silver. The break-even cost of p -type mono-Si PERC cells is ~ 2.3 $-cents/Wp higher than for p -type multi-Si PERC cells, due to the higher cost of the input wafers.